Attitude of couples towards family planning practices in the field practice area of Prathima Institute of Medical Sciences, Karimnagar - Gayathry, Dasari; Moluguri, Anil; Sachin, G.; Sekhar, Chandra (International Journal Of Community Medicine And Public Health, 2018)
Background: Uncontrolled population growth has been a problematic issue all over the world. Knowing the women’s and their husband’s awareness and attitude towards family planning may help us to intervene so that the practice can be increased. This might ensure the right of women to have child as they wish and later reduce unwanted pregnancies and abortions. Hence the present study is concerned with evaluation of attitude of couples towards family planning. Methods: A cross - sectional study was conducted during February 2013 - January 2014 among the couples residing in the field practice study areas. A semi-structured questionnaire consisting attitude of respondents regarding various aspects of family planning was administered to 406 couples of the study area. Results: It has been observed that the females had higher positive attitude scores (16.04±3.641) than males (13.85±4.605) and was statistically significant (p=0.000). Urban residents showed higher positive attitude scores (17.75±2.873) compared with rural (12.14±3.582) and difference was statistically significant (p=0.000). Conclusions: One of the promising findings of the study is, the majority of respondents showed a positive attitude towards contraceptive use. Female respondents and urban population showed more favorable attitude as compared to males and rural population respectively. There is need to target these population for health education interventions in order to achieve the desirable practices.